2022
DOI: 10.1002/esp.5375
|View full text |Cite
|
Sign up to set email alerts
|

Understanding historical earthquakes by mapping coseismic landslides in the Loess Plateau, northwest China

Abstract: Locating the epicenters and quantifying the magnitudes of historical earthquakes are important, yet difficult, tasks. These tasks often entail estimating seismic intensities based on written documentation, which suffers from biases and uncertainties that are difficult to evaluate. However, past strong earthquakes may trigger numerous landslides that remain in the landscape to the present day, whose number and distribution are correlated with the magnitude and location of the earthquakes. Thus, mapping historic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For instance, Xu et al [57] emphasized that visual interpretation based on high-resolution images can identify subtle morphological indicators of landslides, especially in complex terrains. Similarly, Xu et al [58] highlighted the superiority of interpreting ancient landslides based on visual interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Xu et al [57] emphasized that visual interpretation based on high-resolution images can identify subtle morphological indicators of landslides, especially in complex terrains. Similarly, Xu et al [58] highlighted the superiority of interpreting ancient landslides based on visual interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of four secondary faults (Guomatan fault segment S1, Zhangxian fault segment S2, Wushan fault segment S3, and Tianshui-Baoji fault segment S4, from west to east of the WQLF in Figure 1) and has exhibited a slip rate of approximately 2-3 mm/a [17][18][19]. Along the WQLF, a series of typical left-lateral gullies and terraces, fault passes, and ridge dislocations were formed, and multiple significant earthquakes have occurred in history, such as the Longxi M 7 earthquake in 47 B.C., Gangu M 6½ earthquake in 128 A.D. (magnitude classification standard used for historical earthquakes, which uses fractions such as ¼, ½, and ¾ to designate non-integer historical earthquake magnitudes, with an error margin of 1/4), Tianshui M 7 earthquake in 734 A.D., Gangu-Wushan M 6½ earthquake in 1765, and Kangle M 6¾ earthquake in 1936 [10,[20][21][22][23], indicating that the fault has exhibited strong activity throughout the late Holocene. Li et al [24] revealed that the recurrence interval of seismic events on the Zhangxian segment of the WQLF is approximately 2000 years according to paleoseismic trenches.…”
Section: Geological Settingmentioning
confidence: 99%
“…Tectonically, it belongs to the middle-north section of a north-south strong seismic tectonic zone, which contains many late-Quaternary active fracture zones and intense tectonic activity (Lei et al, 2006). According to records, many earthquakes have occurred in Tianshui and its surrounding areas; such events include an M8.0 earthquake, with its epicenter in Tianshui in 1654, and an M7.5 earthquake, with its epicenter in Tongwei in 1718 (Xie et al, 2017;Xu et al,2022). Earthquakes often induce landslide geological disasters and form disaster chains, resulting in a large number of casualties (Yin et al, 2009;Li et al, 2015;sun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%